2005
DOI: 10.1111/j.1365-2915.2005.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Field and laboratory studies on water conditions affecting the potency of VectoBac® (Bacillus thuringiensis serotype H‐14) against larvae of the blackfly, Simulium damnosum

Abstract: River water conditions that might influence the efficacy of VectoBac, a formulation of the microbial insecticide Bacillus thuringiensis H-14 Berliner against Simulium damnosum sensu lato Theobald (Diptera: Simuliidae) larvae were investigated. A standard formulation was assayed 130 times over 15 months using a mini-gutter system at a field station beside the River Pra in Ghana. The lethal concentration (LC) values, river temperature, conductivity, turbidity and pH were analysed using univariate and multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The turbidities of the various media in this experiment ranged from 0.3 to 7.7 NTU, illustrating again that a measurement of turbidity alone is insufÞcient for predicting the outcome of a treatment. This also tends to negate the possibility of kaolinite clay-binding midgut receptors or the proteins thereby reducing efÞcacy as suggested by Wilson et al (2005).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The turbidities of the various media in this experiment ranged from 0.3 to 7.7 NTU, illustrating again that a measurement of turbidity alone is insufÞcient for predicting the outcome of a treatment. This also tends to negate the possibility of kaolinite clay-binding midgut receptors or the proteins thereby reducing efÞcacy as suggested by Wilson et al (2005).…”
Section: Discussionmentioning
confidence: 91%
“…Guillet et al (1985) suggested that when the larval gut is full of particles, there may be reduced ICP ingestion. Wilson et al (2005) found that favorable performance of a commercial product in West Africa was achieved with river turbidities below 4.2 Nephelometric Turbidity Units (NTUs). They speculated that either the Þne mud particles were blocking the mid-gut receptors from the ICPs or that the ICPs were being adsorbed onto the surface of the suspended particles.…”
mentioning
confidence: 99%
“…ceased below a river channel into which large amounts of blasting dust settled (Walsh 1984). The concentrations of silt in 2014 were about 15 times higher than those measured by Wilson et al (2005) in samples collected during 1997-1998 in the lower Pra River at Daboase (5°4°N, 1°39°W) (27.3 mg/l in the dry season and 24.4 mg/l in the rainy season, with turbidities ranging from 4.2 to 72.0 NTU). Their mean turbidity of 23.9 NTU was similar to the turbidity of 13.6 measured in the Okumayemfuo stream in 2014.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding water parameters, in an experiment conducted by Wilson et al (2005) the best mortality results of a Bti-based product against S. damnosum Theobald, 1903 larvae were observed as the temperature increased. According to the authors, temperature influences metabolism and, consequently, greater ingestion of toxins by larvae.…”
Section: Water Parameters and Physical Integrity Of The Collection Sitementioning
confidence: 99%